The Potential of Local Wisdom in Dadio as a Source for Biology Learning - Ilhami, Aldeva; Sriyati, Siti; Liliawati, Winny; Nurbaiti, Nurbaiti; Handrianto, Ciptro (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2024)
Dadio is a traditional food of the Malay community in Kampar, Indonesia, made from fermented buffalo milk using bamboo as a medium. It is consumed as a supplementary food and is an essential part of traditional ceremonies, a practice that continues to this day. This study aimed to understand the dadio-making process among the Malay community in Kampar and analyze the scientific concepts embedded within it. A case study design was employed, focusing on the dadio-making process in Limau Manis Village, Kampar Regency. Data was collected through in-depth interviews, observations, and document analysis. Data analysis was conducted using Miles and Huberman's interactive model, encompassing data collection, reduction, display, and conclusion. The results show that the community uses buffalo milk, tipih manih bamboo (Schizostachyum blumei), and batu banana leaves (Musa Paradisiaca var. balbisiana colla) to make dadio. The process begins with traditional buffalo milking and a 12-hour fermentation process. Dadio has become an identity for the Malay community in Kampar due to its use in traditional ceremonies and as a supplementary food. The community believes that consuming dadio offers health benefits such as managing hypertension and cholesterol and serving as a supplement for pregnant and lactating women. The dadio-making process involves various scientific concepts, including microbial metabolism, microbial diversity, bacterial physiology, plant anatomy and morphology, and fermentation. Thus, it holds potential as a learning resource for biology.